2004
DOI: 10.1039/b411643g
|View full text |Cite
|
Sign up to set email alerts
|

EPR and affinity studies of mannose–TEMPO functionalized PAMAM dendrimers

Abstract: Mannose-TEMPO functionalized G4-PAMAM dendrimers with increasing mannose loadings have been synthesized and characterized by MALDI-TOF MS and EPR spectroscopy. Analysis of linebroadening effects in the EPR spectra of these dendrimers allowed us to determine the relative presentation of mannose and TEMPO on the dendrimer surface. Hemagglutination assays and affinity chromatography/EPR experiments to assess the activity of the mannose-TEMPO dendrimers with Concanavalin A are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Macrophage-specific targeting of mannose-coupled nanoparticles in various tumors has been described earlier, 4547 and mannose-functionalized PAMAM dendrimers have mainly been developed for the study of protein-carbohydrate interactions. 48 Goonewardena et al, however, demonstrated uptake of mannose-conjugated G5 dendrimers by tumor-associated macrophages as well as activated bone marrow-derived monocyte-macrophages. 49 Taking advantage of the high expression of folate receptor on activated macrophages, earlier studies have used folate functionalized nanoparticles for macrophage targeting, 50 and this strategy is currently being favorably considered for rheumatoid arthritis therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage-specific targeting of mannose-coupled nanoparticles in various tumors has been described earlier, 4547 and mannose-functionalized PAMAM dendrimers have mainly been developed for the study of protein-carbohydrate interactions. 48 Goonewardena et al, however, demonstrated uptake of mannose-conjugated G5 dendrimers by tumor-associated macrophages as well as activated bone marrow-derived monocyte-macrophages. 49 Taking advantage of the high expression of folate receptor on activated macrophages, earlier studies have used folate functionalized nanoparticles for macrophage targeting, 50 and this strategy is currently being favorably considered for rheumatoid arthritis therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Isothiocyanates 13 b and 13 d were synthesized from the corresponding amines 12 b and 12 d by following ap rocedure by Munch. [12] Alternatively, amine 9 may also first be converted to the respective thiourea 11 by treatment with thiophosgene (10), [13] followed by addition of the respective amines 12.D epending on the accessibility of isothiocyanates 13,e ither route may be effectively applied. Final desulfuration of 14 with HgOthen gave the desired DCC analogues 1a-d.…”
Section: Resultsmentioning
confidence: 99%
“…Once the glyco-silicas were synthesized, their ability to bind ConA was evaluated as an adequate methodology to characterize and determine their potential applicability as a chromatographic support. It has been previously proven that affinity chromatography is a valuable tool for the analysis of insoluble systems [37] since hemagglutination inhibition studies (HIA) and enzyme-linked lectin assays (ELLA) (that are the usual techniques for the analysis of carbohydrate-protein interactions) are restricted to assays in solution. The characterization was carried out by packing the glyco-silica in a column followed by saturating this column with a ConA solution in HEPES buffer and then washing with HEPES buffer to remove the unbonded protein.…”
Section: Resultsmentioning
confidence: 99%